World Trade Organization Agreement on Trade Facilitation: Assessing the Level of Ambition and Likely Impacts - Shintaro Hamanaka (Asian Development Bank (ADB), 2014)
At the Ninth Ministerial Conference of the World Trade Organization (WTO) held in Bali on 3–6 December 2013, the ministers agreed upon the WTO Agreement on Trade Facilitation (ATF). This paper assesses the level of ambition of the ATF from two angles. First, the use of softening language in each provision is examined. Second, the final agreement is compared against the draft text prepared before the Bali conference. Then, the paper considers the likely legal, economic, capacity-building, and reform-inducing impacts of the ATF.
hdl:11540/1284
Keywords: F13; F53; F55; 330; Agreement on Trade Facilitation (ATF); Capacity building; assistance; obligation; best endeavor